Exploring different perspectives of Social Pedagogy: towards a complex and integrated approach. - Úcar, Xavier (Education Policy Analysis Archives, 2013)
Some characterizations describe social pedagogy as a broad, complex, ambiguous and problematic concept that applies to very different things. This is due to the simplicity of the tools used to approach such a complex area. A change of perspective to interpret social pedagogy as a hybrid and complex subject may transform the alleged deficiencies into strengths and promise. This paper provides elements that enable such a change. To this end, some misunderstandings regarding social pedagogy are presented. These misunderstandings are scenarios and factors that have contributed (1) to the generation of inaccuracies and confusions about what social pedagogy is, could, or should do, and (2) to the projection of an inconsistent and poorly defined image of social pedagogy, i.e. a discipline without method and an ineffective and inefficient practice for solving social problems. The social pedagogy that emerges from the six misunderstandings (cognitive, policy-related, scientist, action-related, normative and social) is complex. From the new perspective, it is more of a hybrid subject (a concept, a discipline and a practice) that is complex, open, dynamic and ever changing.